Spain : The Reform of Spanish Savings Banks Technical Notes. (IMF Staff Country Reports; Country Report ;, 2012)
This technical note assesses the reform of Spanish savings banks (SSBs). It provides a brief overview of the SSB institutional framework before the reform, and describes the main factors that led to the financial distress, albeit uneven, of the SSB sector. The note outlines major regulatory and institutional reforms of SSBs. It evaluates the main achievements of the reforms to date, and also considers improvements to the current framework and potential developments in the SSB institutional framework.